PERAN GURU BK DALAM MENINGKATKAN KECERDASAN INTERPERSONAL PESERTA DIDIK MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMP NEGERI 12 PADANG - Yelvi, Yully Hasmi (Bimbingan dan Konseling, 2014)
This research is motivated by the phenomenon while doing group counseling services inschools, any learners who are less able to establish good relations between groups, how tocommunicate with students who are not polite, less concerned among fellow friends, unable tocontrol himself, lack of cooperation with the group, teasing, lack of mutual appreciation andrespect. This study aimed to describe the role of guidance and counseling teachers in improvinginterpersonal learners viewed from the implementation of group counseling services. Samplingwas performed using total sampling. This study takes students who have followed the guidance ofthe group as the study sample totaling 62 people. The technique used to analyze the data is thepercentage techniques. The results showed: (1) The role of guidance and counseling teachers inimproving interpersonal learners are seen on stage in the establishment of criteria for the role. (2)The role of guidance and counseling teachers in improving interpersonal learners are seen from theintermediate stage to the instrumental sufficient criteria. (3) The role of guidance and counselingteachers in improving interpersonal learners are seen on stage at the criteria for instrumentalactivities. (4) The role of guidance and counseling teachers in improving interpersonal learners areseen on stage at the conclusion of the criteria is quite a role. (5) Guidance and counseling role ofteachers in improving interpersonal learners are seen on stage at the termination criterion plays animportant role.